A 15 year-old-girl with persistent leg pain diagnosed as a giant cell tumor of the tibial diaphysis: A case report and review of the literature. (October 2022) - Masud, Hasan; Yadav, Prashant; Yadav, Sushmita; kamal, Mohammed
Abstract: Introduction: Giant cell tumor (GCT) is a benign bone tumor typically seen in epiphysis or metaphysis of mature long bones. Multiple large multinucleated giant cells dispersed among mononuclear spindle cells and monocytes constitute characteristic histological background of GCT of bone (GCTB). Case presentation: A 15-year-old girl was admitted to our hospital with the complaint of pain and swelling in the left leg with difficulty in walking for 2 years. On X-ray of the left leg, osteolytic, expansile, eccentric lesion with sclerotic bone margin on the diaphysis of the tibia was seen suggesting oesteofibrous dysplasia. MRI demonstrated findings compatible with adamantinoma. The subsequent histology report was rather surprising, consistent with giant cell tumor of the bone. Extended intralesional curettage was done with the help of a high-speed burr followed by chemical cauterization and bone grafting. The patient was followed up for 2 years. The patient could walk normally without assistance or any signs of a recurrence. Discussion: GCTB commonly affects people in their third and fourth decades of life and involves epiphysis of the long bone, but this is a case of diaphyseal GCT, at an age of 15 years. It is challenging to diagnose GCT, if present in an unusual location, unless confirmed by histopathological examinations. Conclusion: A multi-disciplinary approach is required to correctly reach the diagnosis of GCT when it happens to be in an uncommon location(s). Early diagnosis with appropriate treatment and long-term follow-up is mandatory for the successful outcome of the treatment. Highlights: GCTB commonly affects people in their third and fourth decades of life and involves epiphysis of the long bone. We report an unusual case of a 15-year-old girl diagnosed as a giant cell tumor in the diaphysis of the tibia. Early diagnosis, appropriate treatment, and long-term follow-up are essential for a successful treatment outcome. Extended intralesional curettage was performed with the help of a high-speed burr followed by chemical cauterization and bone grafting. After surgery and close monitoring at regular intervals for 2 years, the patient was able to walk normally without any signs of recurrence.